European company survey on reconciliation of work and family life final report - Institut der Deutschen Wirtschaft Koln.; Federal Ministry for Family Affairs, Senior Citizens, Women and Youth (Βερολίνο : Federal Ministry for Family Affairs, Senior Citizens, Women and Youth - BMFSFJ, 2010)
Demographic change requires an increase in labour force participation. This applies particularly to those groups which have had relatively low participation rates in the past and those with family obligations such as child rearing or care for the elderly. With many companies already reporting difficulties in recruiting or retaining qualified staff, policies which aim to reconcile work and family life more effectively have become more attractive. Implementing work-life balance1 policies may therefore be considered a significant factor in the enhancement of corporate competitiveness and national prosperity. Governments together with the social partners at the national, sectoral and company levels must tackle the challenge of ensuring the competitiveness of companies while granting women and men equal participation in work and family life.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Demographic change; Work and family; Electronic books